2013
DOI: 10.1017/s1366728913000497
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring complex structures under minority language conditions: Bilingual acquisition of plural morphology in Welsh

Abstract: This study explored the effects of quantity and quality of input on bilingual children's acquisition of complex plural morphology in Welsh. Study 1 explored the quality of adult input and revealed target-like marking of plural forms in naturalistic adult speech. Study 2 presented eighty-eight 7–11-year-old children, across three bilingual language groups (L1 Welsh, 2L1, and L2 Welsh), with a plural production task. Results revealed performances approaching L1 adult norms among L1 Welsh-speaking bilinguals, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 54 publications
(63 reference statements)
6
67
1
4
Order By: Relevance
“…The plural task showed that both groups were still in the process of acquiring the plural formation patterns in Welsh at the age of 6 years, confirming previous findings on the protracted acquisition rate of the Welsh plural system (Thomas et al . ). This study further revealed that the acquisition of the Welsh plural system is particularly problematic for children with SLI, who differed significantly from their TD peers.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The plural task showed that both groups were still in the process of acquiring the plural formation patterns in Welsh at the age of 6 years, confirming previous findings on the protracted acquisition rate of the Welsh plural system (Thomas et al . ). This study further revealed that the acquisition of the Welsh plural system is particularly problematic for children with SLI, who differed significantly from their TD peers.…”
Section: Discussionmentioning
confidence: 97%
“…This is, for example, the case for the ‐ydd suffix, which adjoins to singular nouns indicating person or object (e.g., gobennydd , ‘pillow’) (Thomas et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, they were only more successful in correctly interpreting bare NPs and not definite NPs. Several studies have found that variations in the input play a role in the rate of acquisition of child L2 learners [26,27] and bilingual children [28][29][30][31][32]. Variation in the input can have an effect on the morphosyntactic domain as well as on the semantic domain [28].…”
Section: Discussionmentioning
confidence: 99%